Calibrating high-precision Faraday rotation measurements for LOFAR and the next generation of low-frequency radio telescopes - Sotomayor-Beltran, C.; Sobey, Charlotte; Hessels, J.; De Bruyn, G.; Noutsos, A.; Alexov, A.; Anderson, J.; Asgekar, A.; Avruch, I.; Beck, R.; Bell, M.; Bell, M.; et al. (EDP Sciences, 2013)
Faraday rotation measurements using the current and next generation of low-frequency radio telescopes will provide a powerful probe of astronomical magnetic fields. However, achieving the full potential of these measurements requires accurate removal of the time-variable ionospheric Faraday rotation contribution. We present ionFR, a code that calculates the amount of ionospheric Faraday rotation for a specific epoch, geographic location, and line-of-sight. ionFR uses a number of publicly available, GPS-derived total electron content maps and the most recent release of the International Geomagnetic Reference Field. We describe applications of this code for the calibration of radio polarimetric observations, and demonstrate the high accuracy of its modeled ionospheric Faraday rotations using LOFAR pulsar observations. These show that we can accurately determine some of the highest-precision pulsar rotation measures ever achieved. Precision rotation measures can be used to monitor rotation measure variations-either intrinsic or due to the changing line-of-sight through the interstellar medium. This calibration is particularly important for nearby sources, where the ionosphere can contribute a significant fraction of the observed rotation measure. We also discuss planned improvements to ionFR, as well as the importance of ionospheric Faraday rotation calibration for the emerging generation of low-frequency radio telescopes, such as the SKA and its pathfinders. © 2013 ESO.